Improving Students Activity and Students Learning Outcomes by Using RTE (Rotating Trio Exchange) Assisted by Five Media - Umi Kulsum Fahriayul Muhlisoh; Fitriana Eka Chandra (Jurnal Axioma : Jurnal Matematika dan Pembelajaran, 2018)
The purpose of the research is to describe the student activities by using RTE (Rotating Trio Exchange) with Lima media. To describe the student learning outcomes by using RTE (Rotating Trio Exchange) with Lima media. The kind of the research is PTK with qualitative and quantitative approach. The subjects of the research are students of class VII at MTs. Kasyiful Ulum. With the data collecting method that used in the research are documentation, observation, interview and test. The data analysis method that used is qualitative and quantitative. The results of the research there is increased activity and student learning outcomes.Keywords: RTE, students activity, and students learning outcomes